The unilateral presidency and the news media : the politics of framing executive power - Major, Mark.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Media coverage of presidential actions can not only serve journalistic purposes, but can also act as a check against unilateral decision making. The book seeks to uncover how the news media has worked to curtail overreaching power within the executive branch, demonstrating how the fourth estate keeps presidential overreach at bay.
Keywords: Political science; Communication; Public policy; Europe -- Politics and government